The Dual-Monetary Policy and Growth of The Real Sector (A Study Case in Indonesia and Malaysia) - Karuni, Mudita Sri; Sunaryati, Sunaryati (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Within a dual banking system, monetary policy is implemented under a regulatory framework. In addition to maintaining price stability, monetary policy aims to influence real economic activity through its transmission mechanism. This mechanism is subject to change due to various financial sector phenomena. The study aims to analyze the relationship between dual-monetary system mechanisms, encompassing conventional interest rates and Islamic returns, and the real sector in Indonesia and Malaysia from 2010 to 2019. Utilizing the Vector Error Correction Model (VECM), the study reveals that in Indonesia, conventional monetary policy significantly impacts the real sector in the short term, while Islamic monetary policy exhibits a stronger long-term influence. Similarly, in Malaysia, Islamic monetary policy demonstrates greater effectiveness in influencing the real sector compared to its conventional counterpart. IRF analysis indicates that Islamic monetary policy demonstrates greater stability than the conventional model in both countries. Furthermore, FEVD analysis suggests that the implementation of a dual-monetary policy, incorporating both conventional and Islamic models, promotes real sector growth in Indonesia. Conversely, in Malaysia, a dual-monetary policy relying solely on the conventional model appears to hinder real sector growth. Overall, Islamic monetary policy in Malaysia proves more effective in stimulating the real sector.